Factors That Influence Customer’s Decisions In Choosing Sharia Bank Services In Kampar District Of Riau - Pertiwi Indah Darmawan (UIN Siber Syekh Nurjati Cirebon, 2023)
The difference in customer interest in choosing between conventional banks and Islamic banks is very clear in Air Tiris Village, Kampar District, Kampar Regency. In Air Tiris Sub-District, there are several conventional banks and one Islamic bank. Customers are a source of bank funds (third party funds) and the size of the number of customers influences the success of the bank's business, especially in obtaining profits through financing mechanisms. The lack of public interest in saving at Islamic banks is thought to be influenced by various factors. This research was conducted using the case study method. The sample in the study was 40 peoples selected by convenience. Data were analyzed using multiple linear regression analysis. Factors that have a significant influence on customer decisions in choosing financial services at PT. BPRS Berkah Dana Fadhlillah (Perseroda), namely products, knowledge and promotions. Service and location factors have no significant effect. The most dominant factor is the product, with the largest and most significant coefficient.Keywords: product, knowledge, promotion, service, location, customer.